A Structural Equation Modelling (SEM) approach on Construction Noise Related Perception and Behavior among the Workforces - K. C. Vinu Prakash; K. Yogeswari (Civil Engineering Journal, 2022)
Noise pollution from the construction industry is unpredictable and harmful to workers over the long term. There has been a lot of research on noise pollution at construction sites throughout the world, but India lacks research on construction noise and its perceived impacts on workers. This study aims to look into how Indian construction workers perceive noise and behave to protect themselves. From previous research, the noise-related perception parameters were identified and a questionnaire was created. In the questionnaire survey, 520 responses from white- and blue-collar workers were gathered. The SPSS tool was used to analyze the responses. The Pearson correlation analysis determined how closely the perception parameters are associated. The relationship between noise sensitivity and involvement in preventive measures, as well as awareness perception, was also supported by structural equation modeling. The study’s findings thus revealed that workers' behaviour can be influenced depending on their level of awareness. The implications of the findings help to improve our theoretical understanding of how construction workers involve in preventive measures and will aid in the development of safety policies and training programs to increase worker knowledge and curb risk-taking behaviour. The study's novelty lies in the development of a framework for construction noise assessment and abatement in India that is suggested and validated by construction industry professionals in real time projects. Doi: 10.28991/CEJ-2022-08-12-04 Full Text: PDF